86.8k views
4 votes
Find the 14th term of the arthmetic sequence x-1, 7x -7 , 13x-13,....

User Manismku
by
4.9k points

1 Answer

4 votes

Since they're in arithmetic progression, there is a constant difference between consecutive terms of


(7x - 7) - (x - 1) = 6x - 6

Recursively, the sequence is given by


\begin{cases} a_1 = x-1 \\ a_n = a_(n-1) + 6x - 6 & \text{for }n\ge2\end{cases}

By substitution, we have


a_2 = a_1 + 6x-6


a_3 = a_2 + 6x-6 = a_1 + 2(6x-6)


a_4 = a_3 + 6x-6 = a_1 + 3(6x-6)

and so on, up to the 14th term


a_(14) = a_1 + 13(6x-6)


a_(14) = (x-1) + 78 (x - 1)


a_(17) = 79 (x - 1) = \boxed{79x-79}

User Kern
by
5.7k points